United for Humanity: Developing a Collaborative Model for Crowd Engagement in Crisis Recovery Campaigns - Pestana, Maria Clara; Vieira, Vaninha (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2024: Anais do XIX Simpósio Brasileiro de Sistemas Colaborativos, 2024)
The response to humanitarian crises involves unpredictable challenges faced by aid agencies. This research explores collaboration among entities and crowd engagement in the recovery of communities affected by crises and emergencies, focusing on the collaborative aspects of crowdfunding platforms. Crowdfunding has proven effective in rapidly raising funds, increasing public awareness, and identifying assistance needs during emergencies. This work proposes the analysis of a crowdfunding platform to enhance crowd engagement and collaboration between citizens and response entities in crisis recovery campains.